STUDY OF HYBRID ANNUITY MODEL ON TOLL ROAD IN INDONESIA - TRIARSANI RAMADHANTI, DIZKA
Indonesia strives for toll road connectivity to push the high logistics costs and lead to economic growth. However, the expansion of toll road construction on a large-scale has cost much money. So, an innovative funding scheme must be developed to attract the private to invest in those projects. Hybrid Annuity Model is a new public-private partnership developed by the Government of India in 2016 to reduce concessionaires’ risk on toll road project funding. This study aimed to examine the compatibility of the Hybrid Annuity Model implementation on Indonesia toll road. The analysis was carried out through financial feasibility and sensitivity analysis on Serang – Panimbang toll road as the object study. Moreover, a survey was conducted to know the stakeholders’ perception of this funding scheme implemented in Indonesia. The results showed that Hybrid Annuity Model could give financial feasibility on Serang – Panimbang toll road under any changes of traffic volumes, toll fares, discount rates, investment costs, investment return period, and the investment proportion between the Government and the concessionaires. From stakeholders’ perspective, Hybrid Annuity Model could be implemented on Indonesia toll roads, especially those which were not financially feasible and located in rural areas. Furthermore, it needed some improvements and supporting regulations to be more suitable applied on Indonesia toll road.